Integrated School Leadership Strategies Based on Local Programs for Teacher Competency Development - Herlina Nuraini Adinengtias Nita Ekasari; Afiful Ikhwan; Devid Dwi Erwahyudin (JIE (Journal of Islamic Education), 2026)
This study aims to analyse the implementation and effectiveness of the principal's leadership strategy in developing teacher competency at SDN Gupolo Ponorogo. The study used a qualitative approach with a case study design to gain an in-depth understanding of the leadership strategies applied in the elementary school context. Data collection was conducted through participant observation, semi-structured interviews, and documentation. Research informants consisted of the principal, class teachers, and Islamic Religious Education (PAI) teachers who were purposively selected based on their involvement in school programs. The researchers analysed the data using the interactive model through the stages of data reduction, data presentation, and conclusion drawing. They also tested data validity through source and technique triangulation. The results showed that the principal implemented leadership strategies in a planned, systematic, and sustainable manner through motivation, academic supervision, internal and external training, and integration of local wisdom-based school programs. To implement these strategies, the principal integrated the school's vision and mission into various educational programs, such as religious activities, reog performances, and routine sports involving teachers. The implementation of these leadership strategies proved effective in improving teachers' pedagogical, professional, and social competencies. These improvements are evident in teachers' ability to manage learning more systematically, increased participation in professional development, and the development of communication and collaboration skills through involvement in school activities. Furthermore, the integration of local wisdom-based programs provides a more contextual and meaningful learning experience for both teachers and students. Local culture-based activities not only serve as a means of cultural preservation but also serve as a medium for holistic teacher competency development. Research findings indicate that leadership strategies integrated with school culture and local programs can create a professional learning environment that supports continuous improvement in educational quality. Therefore, principal leadership strategies based on local programs can be a relevant approach to developing teacher competency in elementary schools.